Numerical analysis of liquid-solid adsorption model - Leonavičienė, Teresė; Čiegis, Raimondas; Baltrėnaitė, Edita; Chemerys, Valeriia (Mathematical Modelling and Analysis, 2019)
In this paper, the numerical algorithms for solution of pore volume and surface diffusion model of adsorption systems are constructed and investigated. The approximation of PDEs is done by using the finite volume method for space derivatives and ODE15s solvers for numerical integration in time. The analysis of adaptive in time integration algorithms is presented. The main aim of this work is to analyze the sensitivity of the solution with respect to the main parameters of the mathematical model. Such a control analysis is done for a linearized and normalized mathematical model. The obtained results are compared with simulations done for a full nonlinear mathematical model.